PENCEGAHAN PERUBAHAN WARNA PADA KAYU JAMUJU (Podocarpus imbricatus) DAN KISAMPANG (Evodia aromatica BL) DENGAN BAHAN DASAR DESINFEKTAN - Agus Ismanto; Mohamad Iqbal (Jurnal Penelitian Hasil Hutan, 2013)
The aim of this research was to study natural discoloration of jamuju (Podocarpus imbricatus) and kisampang (Evodia aromatica BIL..) before and after treatment again of temperature, bumidity, and beat. Discoloration prevention conducted chemically by using antiseptic containing benzalkonium klorida (formula C), kresol or asam kresilat (formula D) and methylene bistiryiocyanate (MBT as comparison) either on log that is planed or unplaned and on sawn timber. The MBT efficacy result on jamuju and kisampang sawn timber, and formula Con kisampang timber show that it can prevent blue stain with four weeks protection period. Measurement result for brightness colour of jamuju timber on the planed is about 35,22 (MBT Under the roof-45,22 (CAC) and 10,62 (C outside)-37,14 (KAC) on the unplaned. Whereas, measurement for brightness colour of kisampang timber on the planed is about 45,04 (CAC)-53,42 (K Outside) and 8,24 (MBT Outside)-46,66 (KAC) from standard value 73,5. Measurement result for total colour variation of AE kisampang timber on the planed is about 8,80 (K outside)-22,56 (K Under the roof) and 21,57 (DAC)-40,19 (C Outside) on the unplaned. Whereas AE* of jamuju timber on the planed is about 20,49 (MBT Outside)-25,65 (DAC) and 23 (CAC)-41,02 (C. Outside) on the unplaned.